PEMANFAATAN INSENTIF PAJAK, SANKSI PAJAK, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK SAAT PANDEMI COVID-19 - Valencia; Mulyani Mulyani (Jurnal Akuntansi, 2023)
Tax is one of the components of state revenue, and taxes play an important role in national development and government spending. But the public's compliance to carry out their tax obligations is still low, plus the current situation faced by the Covid-19 pandemic, which can be seen from the realization of tax revenues in 2020 of 89.25% of the target set. This study aims to prove the effect of the use of tax incentives, tax sanctions, and taxpayer awareness on taxpayer compliance. This study uses a questionnaire distributed to taxpayers who are MSMEs in Jambi City. Then the data will be processed using the SPSS 26 program to test the validity, reliability, classical assumption test, and hypothesis testing. The results of the research on the t statistic test have a sig value. The variable of the use of tax incentives is 0.043, the tax penalty is 0.000, and the awareness of the taxpayer is 0.286. The conclusion obtained from the results of this study is that the use of tax incentives and tax sanctions has a positive effect on taxpayer compliance during the Covid-19 pandemic, while taxpayer awareness has no effect on taxpayer compliance during the Covid-19 pandemic.